SERINE ARGININE PROTEIN KINASE-1 (SRPK1) INHIBITION AS A POTENTIAL NOVEL TARGETED THERAPEUTIC STRATEGY IN PROSTATE CANCER - Mavrou, Athina (Oncogene, 2014)
Angiogenesis is required for tumour growth and is induced principally by VEGF-A. VEGF-A pre-mRNA is alternatively spliced at the terminal exon to produce two families of isoforms, pro- and anti-angiogenic, only the former of which is upregulated in prostate cancer. In renal epithelial cells and colon cancer cells, the choice of VEGF splice isoforms is controlled by the splicing factor SRSF1, phosphorylated by SRPK1. Immunohistochemistry staining of human samples revealed a significant increase in SRPK1 expression both in prostate intra-epithelial neoplasia lesions as well as malignant adenocarcinoma compared to benign prostate tissue. We therefore tested the hypothesis that the selective upregulation of pro-angiogenic VEGF in prostate cancer may be under the control of SRPK1 activity. A switch in the expression of VEGF(165) towards the anti-angiogenic splice isoform, VEGF(165)b, was seen in PC-3 cells with SRPK1 knock-down (KD). PC-3 SRPK1-KD cells resulted in tumours that grew more slowly in xenografts, with decreased microvessel density. No effect was seen as a result of SRPK1-KD on growth, proliferation, migration and invasion capabilities of PC-3 cells in vitro. Small molecule inhibitors of SRPK1 switched splicing towards the anti-angiogenic isoform VEGF(165)b in PC3 cells and decreased tumour growth when administered intraperitoneally in an orthotopic mouse model of prostate cancer. Our study suggests that modulation of SRPK1 and subsequent inhibition of tumour angiogenesis by regulation of VEGF splicing can alter prostate tumour growth and supports further studies into the use of SRPK1 inhibition as a potential anti-angiogenic therapy in prostate cancer.